A review of conventional and drug-eluting chemoembolization in the treatment of colorectal liver metastases: principles and proof. (May 2015) - Liu, David M; Thakor, Avnesh S; Baerlocher, Mark; Alshammari, Mohammed T; Lim, Howard; Kos, Sebastian; Kennedy, Andrew S; Wasan, Harpreet
ABSTRACT : The management of colorectal liver metastasis has undergone a significant change since the development of novel ablation and embolization. Drug-eluting microsphere platforms, designed to deliver targeted concentrations of systemic therapy directly into the tumor via its arterial vasculature, have garnered interest and gained in popularity in recent years. Based on in vitro and in vivo data, multiple factors contribute to locoregional exposure including carrier base, smaller particle size (larger surface area), chemotherapeutic and chemotherapeutic intensity. Based on the current published clinical data, therapy appears well tolerated but the questions remain as to the ideal technique, patient population and overall efficacy. The purpose of this article is to provide a perspective on the scientific basis, and clinical review of the current data supporting the use of this platform in the setting of metastatic colorectal carcinoma.